SANKSI PIDANA MATI TERHADAP PELAKU TINDAK PIDANA KORUPSI DI INDONESIA DALAM PARADIGMA YANG SERSIFAT PLURALISTIK - Eko Ari Wibowo (JURNAL SUMBER HUKUM, 2025)
Abstract The death penalty for corruption crimes in Indonesia is basically regulated in the provisions of Article 2 of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption. In the provisions of this formulation, it seems that the death penalty sanction policy in Indonesia is experiencing legal problems, because legally the provisions of the death penalty sanction in Indonesia are not formulated clearly, thus obscuring the views of law enforcers in Indonesia. The research method used in this study is normative sociological legal research. The results of this study reveal a policy formulation for the death penalty that is ambiguous in its formulation but clearly visible in its legal interpretation. So basically, law enforcers can apply the death penalty to perpetrators of corruption in Indonesia. From a pluralistic perspective, criminal acts of corruption occur due to neglect of the wider community, especially in the process of holding elections in Indonesia, thus giving rise to criminal acts of corruption in the future by leaders and representatives of the people in Indonesia. Keywords: Corruption, Paradigm, Pluralism.